Built environment and travel behavior in rural areas: A scientometric literature review - Ao, Yibin; Li, Mingyang; Ding, Xuan; Zheng, Junjie; Xiao, Shan; Deng, Shulin; Zhang, Zijun; Wang, Yan; Wang, Tong; Martek, Igor (Frontiers in Ecology and Evolution, 2022)
With the rise of global urbanization, the rural fabric has undergone tremendous changes. As such, the rural built environment impacts on residents’ daily travel behavior is getting more researchers’ attention. To date, most of the research focuses on urban areas in developed countries. To understand the state-of-the-art of interplay between the rural built environment and travel behaviors and to identify future research directions, this study adopts a science mapping approach to identify the relevant topics, authors, journals, and countries of the research done. This study proceeds through bibliometric retrieval of articles from 2005, followed by scientometric analysis and qualitative discussion. 37 documents are found to compare urban and rural domains, with 28 on the rural built environment. Research gaps and the research trends are discussed, of which the main themes are multi-dimensional correlation comparison of rural transportation service systems and emerging transportation modes, the influence of rural social and cultural factors on travel behavior, and low-carbon sustainable transportation. This review provides empirical foundation for current state-of-the-art and identifies the future research directions, specifically for rural built environment impact on travel behavior.